2021
DOI: 10.3390/foods10040770
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the Brining Time in Parmigiano Reggiano Cheese Production Minimally Affects Proteolysis, with No Effect on Sensory Properties

Abstract: Brine soaking is one of the most important steps in the production of Parmigiano Reggiano cheese, since it determines the amount of salt in the final product. Reduction in salt in Parmigiano Reggiano cheese might be important for improving its nutritional profile, but it could affect the manufacturing processes by altering proteolysis and consequently the product quality. In this study, for the first time, salt reduction was explored at the industrial level on real cheese samples manufactured in a local dairy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The presence of these peptides has been reported in various fermented milk products, the antihypertensive effect of which has been proved by various in vitro and in vivo (animal and human trials) experiments [ 33 ]. Considering that in a previous study we evidenced that the sensory profiles were remarkably similar in C- and Hypo-PRC, without any off-flavor development [ 10 ], our results confirmed that reduction of salt content in ripened PRC represents a promising strategy to reduce Na intake, potentially protecting consumers’ health. In this light, the evaluation of the actual ACE-inhibitory activity of digested C- and Hypo-PRC deserves further studies in biological systems.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The presence of these peptides has been reported in various fermented milk products, the antihypertensive effect of which has been proved by various in vitro and in vivo (animal and human trials) experiments [ 33 ]. Considering that in a previous study we evidenced that the sensory profiles were remarkably similar in C- and Hypo-PRC, without any off-flavor development [ 10 ], our results confirmed that reduction of salt content in ripened PRC represents a promising strategy to reduce Na intake, potentially protecting consumers’ health. In this light, the evaluation of the actual ACE-inhibitory activity of digested C- and Hypo-PRC deserves further studies in biological systems.…”
Section: Discussionsupporting
confidence: 84%
“…All peptides detected in not digested PRC were almost completely degraded during gastric digestion, and new bioactive sequences were released. In digested samples, most identified sequences derived from the hydrolysis of high molecular weight peptides already identified in undigested cheese [ 10 ] and from the cleavage of intact α- and β-casein and whey proteins. At the end of gastric digestion, a total of 10 bioactive peptides originated from β-casein, αS1-casein, and αS2-casein, confirming the high affinity of pepsin for these proteins [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2021). Then, UPLC‐MS analyses were performed by applying all the instrumental parameters described in a previous study (Loffi et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%